PENGARUH LOVE OF MONEY, LITERASI KEUANGAN DAN AKSES FINANCIAL TECHNOLOGY TERHADAP PERILAKU INVESTASI GEN-Z DI KOTA DENPASAR YANG DIMODERASI OLEH RISK AVERSION - Yossa Adi Partama; Putu Sri Arta Jaya Kusuma (Faculty of Economics and Business, Universitas Warmadewa, 2025)
This study aims to analyze the effect of love of money, financial literacy, and access to financial technology on investment behavior among Generation Z in Denpasar, with risk aversion as a moderating variable. The study respondents are 180 Generation Z individuals in Denpasar, with data collected through a questionnaire. The data was analyzed using SEM-PLS with the SmartPLS 3 software application. The results show that love of money and financial literacy significantly positively affect investment behavior. In contrast, access to financial technology significantly negatively affects investment behavior. Risk aversion weakens the impact of the love of money and strengthens the effect of financial literacy and access to financial technology on investment behavior, although not all effects are significant. This study highlights the importance of financial literacy and risk aversion in supporting investment behavior, as well as the limitations of technology access without financial literacy.